2016
DOI: 10.1111/liv.13256
|View full text |Cite
|
Sign up to set email alerts
|

Direct antiviral agent treatment of chronic hepatitis C results in rapid regression of transient elastography and fibrosis markers fibrosis‐4 score and aspartate aminotransferase‐platelet ratio index

Abstract: Patients with SVR after DAA therapy showed significant regression of TE values. Rapid decrease in TE was in concordance with regression of validated fibrosis scores FIB-4 and APRI. It remains to be examined whether this indicates a true regression of fibrosis or merely resolution of chronic liver inflammation with subsequent improvement of TE values and laboratory parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
179
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(220 citation statements)
references
References 26 publications
33
179
2
6
Order By: Relevance
“…Also in this study we found significant regression in fibroscan value detected in all patients at the end of treatment and 6 months post-treatment, also the study done by Jacqueline et al, 2017 showed that patients with SVR after DAA therapy showed marked improvement in median transient elastography values from 12.65 kPa to 8.55kPa (8).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Also in this study we found significant regression in fibroscan value detected in all patients at the end of treatment and 6 months post-treatment, also the study done by Jacqueline et al, 2017 showed that patients with SVR after DAA therapy showed marked improvement in median transient elastography values from 12.65 kPa to 8.55kPa (8).…”
Section: Discussionsupporting
confidence: 61%
“…(7) And this was proved by significant regression of the parameters of transient elastography after SVR. (8) Fibroscan is used to determine the degree of liver fibrosis but, its role in assessment of PH and prediction of varices is controversial. (9) Also, Color Doppler ultrasound can be used noninvasively to assess the degree of inflammation and fibrosis in patients with chronic viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Also median FIB-4 and APRI values significantly decreased. In conclusion the authors asked themselves if the rapid decrease of TE measurements, which was in concordance with the significant decrease in the biologic fibrosis scores was linked entirely to a decrease of fibrosis, or it was also due to the resolution of the inflammation following SVR [8].…”
Section: Resultsmentioning
confidence: 99%
“…A German study evaluated a cohort of 392 HCV patients treated with IFT [8]. Transient elastography values, APRI score and FIB-4 were recorded prior to IFT and at 18 months after therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation